Recurrent Unilateral Hemorrhagic Pleural Effusion: A Rare Manifestation of Thoracic Endometriosis Syndrome - Dogra, Neeti (Ann Card Anaesth, 2020)
Unilateral recurrent pleural effusions are commonly encountered in critical care practice. Relevant clinical history, physical examination, radiology, and diagnostic thoracentesis usually identify the cause of pleural effusion in most cases. Thoracoscopy or video-assisted thoracic surgery may be required in selective cases. We report a case of 32-year-old female with recurrent unilateral hemorrhagic pleural effusion that was the presenting feature of thoracic endometriosis syndrome.